Intramolecular dehydrogenative C–S bond coupling of thioamides to form 1, 3-benzothiazines under metal-free conditions. Issue 13 (13th March 2019) - Wen, Li-Rong; Zhou, Cheng-Cheng; Zhu, Ming-Zhe; Xie, Shu-Guang; Guo, Wei-Si; Li, Ming
Abstract : A new protocol for the synthesis of 1, 3-benzothiazines was developed through direct intramolecular dehydrogenative C–S bond coupling. Abstract : A novel HTIB-promoted direct intramolecular dehydrogenative C–S bond coupling reaction of thioamides has been developed to provide 1, 3-benzothiazine derivatives in good yields. The reaction proceeds smoothly to reach completion at room temperature within 1 min under metal-free conditions. This protocol provides a mild and efficient strategy for the synthesis of six-membered N, S-containing heterocycles. Preliminary mechanistic studies indicate that a spirocyclic intermediate might be involved.